A different glimpse into mobilities: On the interrelations between daily spatial mobility and social mobility. Issue 5 (20th October 2017) - Fortunati, Leopoldina; Taipale, Sakari
ABSTRACT: We explore the link between daily spatial mobility and social mobility, taking changes in the contemporary labor market and family as examples. We propose a new theoretical approach to mobility that is defined as a productive force of social labor. Analyzing the relationship between daily spatial mobility and social mobility, we show that spatial mobility has become a strategy of compensation for the lack of social mobility. Explanations for the increase in daily spatial mobility are also provided. Lastly, we reveal how spatial mobility has the capacity to produce major social change, taking the family as an example.